DIGITAL TRANSFORMATION OF ACCOUNTING AND AUDITING BASED ON MODERN INFORMATION SYSTEMS - Yankovska К. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2025)
The article explores the essence of digital transformation in accounting and auditing within the broader context of global economic digitalisation and the active integration of innovations in financial information management. It argues that traditional approaches to accounting and auditing are becoming increasingly ineffective due to the rising volume of data, the necessity for timely decision-making, and the growing demands for transparency in reporting. The study investigates the impact of modern information systems, including ERP solutions, cloud platforms, artificial intelligence, and machine learning technologies, on the automation of accounting processes and the enhancement of financial information quality. It analyses the advantages of cloud technologies, such as real-time access, reduced IT infrastructure costs, and the ability to integrate with other digital services. The article also highlights international experiences in implementing Standard Business Reporting (SBR) in countries with advanced digital infrastructures. Furthermore, it describes the state of digitalisation within the accounting sector in Ukraine, considering various industry and organisational differences. Particular emphasis is placed on the transformation of auditing, where tools such as Big Data, anomaly detection algorithms, blockchain, and digital platforms from leading auditing firms are increasingly utilised. The key benefits of digitalising auditing procedures are outlined, including improved accuracy, enhanced transparency, increased speed, and greater analytical depth of audits. However, the article also addresses several challenges, such as the necessity for digital competencies, the assurance of cybersecurity, adaptation to regulatory changes, and compliance with professional ethics. It posits that the digital transformation of accounting and auditing is not simply a technical upgrade but represents a strategic developmental direction, necessitating the integration of technological innovations, government support, and updated educational approaches.